MANAGEMEN KEAMANAN SEKOLAH ANTI BULLYING ATAU KEKERASAN DI SMA NEGERI 6 SURAKARTA - Latunusa Ambawani, Cettra Shandilia; Mulya Kusuma, Thitha Meista; Kusumastuti, Nofi Animah; Sutama, Sutama; Fathoni, Achmad (ITB AAS Indonesia Surakarta, 2024)
The rise of bullying cases encourages research with the theme of anti-bullying school security management or violence by choosing a research site at SMA Negeri 6 Surakarta because is one of the child-friendly and adipangastuti schools that is very concerned about the comfort and safety of students. The research objective is to describe the planning, implementation and evaluation of anti-bullying or violence school security at SMA Negeri 6 Surakarta. The approach used is a qualitative case study. The sampling technique used purposive sampling. Data analysis techniques used include data reduction, data presentation and conclusion drawing. The results of the research are: (1) Anti-bullying or violence school security planning by forming a violence prevention and handling team, preparing programs, creating links and complaint contacts, and maximising the role of Counselling Guidance (BK); (2) Implementation of anti-bullying or violence school security includes socialisation, implementing work programs and coordination between teams, monitoring links and complaint boxes, enforcing school rules, optimising extracurricular and co-curricular activities, building effective communication, and maximising picket officers; (3) Evaluation of anti-bullying or violence school security is carried out by the internal team and by the external team at the end of each semester, with obstacles in understanding bullying, the realisation of monitoring once a month and lack of coordination. The solution is to make positive activities in the form of competitions, monitoring activities prioritising quality over quantity and increasing coordination between the violence prevention and handling team, order and adipangastuti school. Keywords : Management, Security, Bullying, Violence